Kenya 2023 - Duthie, Shawn; Githere, Neema; Musau, Mwende Mutuli; Nyabola, Nanjala; Olum, Julie (Lonely Planet guidebooks., 2023)
Lonely Planet's Kenya is our most comprehensive guide that extensively covers all the country has to offer, with recommendations for both popular and lesser-known experiences. Gaze at a million wildebeest migrating across Masai Mara; get close to big cats; or hike through the national parks; all with your trusted travel companion.